Penerapan Asas Proporsionalitas Dalam Kontrak Komersial Pada Jasa Konstruksi - Wahyu Susanto; Heru Sandika; Arga J. P. Hutagalung (Universitas Medan Area, 2021)
This study aims to find out how the application of the principle of proportionality in commercial contracts on construction services and in line with the government's objectives in establishing a regulation related to construction services provided as a form of government appreciation in providing legal protection for clients or partners of the company's cooperation. The research method used is normative juridical law research based on secondary legal materials. This research uses the statute approach, conceptual approach, and case approach. The technique of tracing legal materials uses document study techniques, and analysis of studies using qualitative analysis. The results of the study indicate that the proportional principle is the principle that underlies or underlies the exchange of rights and obligations of the parties according to their proportion or share in the entire contractual process. The principle of proportionality ensures that the exchange of wills in the contract, which includes 3 stages (pre-contract, contract, and post-contract) can take place fairly according to the proportions of each party. So that with the application of the principle of proportionality, it is hoped that the agreement can be guarded into a fair agreement according to the proportions of each party